Engaging Generation Z with Virtual Heritage: How Authenticity and Telepresence Drive Continuance Intention - Abas, Novel Idris; Puspawati, Dewita; Mardalis, Ahmad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In response to the declining interest of Generation Z in heritage tourism, Virtual Reality (VR) technology offers a promising solution to revive cultural appreciation. This study aims to test a behavioral model that explains the driving factors of continuance intention towards virtual heritage tourism platforms among this demographic. Adopting the Stimulus-Organism-Response (S-O-R) framework, quantitative data were collected from 195 Generation Z respondents in Indonesia through an online questionnaire and analyzed using PLS-SEM. The analysis results show that authenticity and interactivity (stimulus) have a significant positive effect on continuance intention (response), both directly and indirectly through the key mediating role of telepresence (organism). Specifically, authenticity was found to be the strongest predictor in creating telepresence. This study concludes that to ensure long-term engagement, virtual heritage experiences must focus on providing authentic and immersive content, instead of simply relying on the novelty of the technology itself.